2006
DOI: 10.1007/s00264-006-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

A long-term follow-up of 60 Lord total hip arthroplasties in rheumatic disease: a mean follow-up of 14 years

Abstract: The aim of the study was to analyse the survivorship of 60 total hip arthroplasties using the cementless Lord prosthesis in 51 patients with inflammatory joint disease. Patients were operated on between the years 1985 and 1988. The mean follow-up time was 13.8 (4.0-18.6) years. During the follow-up, one deep infection was encountered, and seven patients died of causes unrelated to the hip replacement. Revision surgery or death of the patient was used as an end point. The overall survival was 88.1% [95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…1 , 2 ): Table 2 shows the failure rates for aseptic loosening per 100 years of ‘hips at risk’. Six studies reported failure rates higher than one (the NICE criteria) [ 20 , 22 , 31 34 ]. Figure 1 displays the results of the comparative studies with the ratio of failure between cementless and cemented cups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , 2 ): Table 2 shows the failure rates for aseptic loosening per 100 years of ‘hips at risk’. Six studies reported failure rates higher than one (the NICE criteria) [ 20 , 22 , 31 34 ]. Figure 1 displays the results of the comparative studies with the ratio of failure between cementless and cemented cups.…”
Section: Resultsmentioning
confidence: 99%
“…Aseptic loosening: six studies showed poor results of cementless cups in RA, one comparative study [ 20 ] and five case series [ 22 , 31 34 ]. In five of these studies with poor result, the smooth threaded cup design was blamed.…”
Section: Discussionmentioning
confidence: 99%
“…At 1988, Lord reports favorable results, an experience over ten years in a series of 2688 personal cases [3] . Most authors confirmed the excellent survival rate of the femoral component at long-term follow-up, and the poor results associated to the threaded acetabular cup [1] , [4] , [5] . Lord THA was abandoned at 1987 in our Orthopedic Department, due to the high failure rate of the threaded cup by aseptic loosening.…”
Section: Introductionmentioning
confidence: 76%
“…Первинне тотальне ендопротезування кульшового суглоба (ТЕКС) зараз є класичною процедурою, яку виконують хірурги-ортопеди в усьому світі, проте деякі випадки залишаються складними та потребують особливого підходу до виконання хірургічного втручання [1]. До цих складних випадків належить ендопротезування в умовах кісткових дефектів кульшової западини вродженого (диспластичного) [2] та придбаного (унаслідок травм, запальних захворювань кульшового суглоба, ятрогенних тощо) [3][4][5] генезу. Складність ендопротезування при цьому полягає в досягненні як первинної, так і тривалої вторинної стабільної фіксації ацетабулярного компонента ендопротеза в кульшовій западині.…”
Section: вступunclassified
“…C. C. Lybаck і співавт. [3] показали виживаність ацетабулярного компонента в умовах ревматоїдного артриту в 64 % випадків (спостереження до 15 років після операції).…”
Section: результати та їх обговоренняunclassified